Diagnostic contribution and therapeutic perspectives of transcranial magnetic stimulation in dementia. Issue 10 (October 2021) - Di Lazzaro, Vincenzo; Bella, Rita; Benussi, Alberto; Bologna, Matteo; Borroni, Barbara; Capone, Fioravante; Chen, Kai-Hsiang S.; Chen, Robert; Chistyakov, Andrei V.; Classen, Joseph; Kiernan, Matthew C.; Koch, Giacomo; et al.
Highlights: This review presents the contribution of TMS to the management of dementia. TMS can be used as a biomarker of the excitability and function of cerebral cortex in dementia. Increasing evidence supports the beneficial effects of rTMS in Alzheimer's disease-related dementias at mild/early stage. Abstract: Transcranial magnetic stimulation (TMS) is a powerful tool to probe in vivo brain circuits, as it allows to assess several cortical properties such as excitability, plasticity and connectivity in humans. In the last 20 years, TMS has been applied to patients with dementia, enabling the identification of potential markers of the pathophysiology and predictors of cognitive decline; moreover, applied repetitively, TMS holds promise as a potential therapeutic intervention. The objective of this paper is to present a comprehensive review of studies that have employed TMS in dementia and to discuss potential clinical applications, from the diagnosis to the treatment. To provide a technical and theoretical framework, we first present an overview of the basic physiological mechanisms of the application of TMS to assess cortical excitability, excitation and inhibition balance, mechanisms of plasticity and cortico-cortical connectivity in the human brain. We then review the insights gained by TMS techniques into the pathophysiology and predictors of progression and response to treatment in dementias, including Alzheimer's disease (AD)-related dementias and secondary dementias. We show that while a single TMS measure offers low specificity, the use of a panel of measures and/or neurophysiological index can support the clinical diagnosis and predict progression. In the last part of the article, we discuss the therapeutic uses of TMS. So far, only repetitive TMS (rTMS) over the left dorsolateral prefrontal cortex and multisite rTMS associated with cognitive training have been shown to be, respectively, possibly (Level C of evidence) and probably (Level B of evidence) effective to improve cognition, apathy, memory, and language in AD patients, especially at a mild/early stage of the disease. The clinical use of this type of treatment warrants the combination of brain imaging techniques and/or electrophysiological tools to elucidate neurobiological effects of neurostimulation and to optimally tailor rTMS treatment protocols in individual patients or specific patient subgroups with dementia or mild cognitive impairment.